A tribute to Victor H. Gonzalez: Twenty years of melittological contributions. - Engel, Michael S. (Journal of Melittology, 2017)
In celebration of the 40th birthday of Victor H. Gonzalez, melittologist and founding assistant editor of the Journal of Melittology, we provide here a brief biographical sketch and summary of his contributions to melittological science during his 20 years of active research. We tabulate his 154 publications (including published abstracts and reviews), along with his 99 species-, six genus-, and one family-group names (all but three have been for bees).